Exploring The Relationship Between Entrepreneurial Networking, Entrepreneur Leadership, Innovation capability, and MSMEs Performance - Murtini Murtini; Abdul Azis Safii; Latifah Anom (Trescode Green Organization, 2024)
This research aims to determine the role of entrepreneurial networks, entrepreneur leadership, on innovation capabilities and MSME performance. The sampling technique used purposive sampling, obtaining a total of 247 samples of MSME owners in the culinary sector in Bojonegoro City. Research data was analyzed using SEM techniques with AMOS software. The research results show that entrepreneurial networking has a positive effect on the innovation ability and performance of MSMEs. Meanwhile, entrepreneurial leadership has no effect on the innovation ability of MSMEs, but has a positive influence on MSME performance. The implications of this research are that the development of entrepreneurial networks can be a crucial factor in enhancing innovation capabilities and performance for Micro, Small, and Medium Enterprises (MSMEs) owners in the culinary sector in Bojonegoro City. Additionally, entrepreneurial leadership also plays a significant role in improving the performance of MSMEs, even though it does not have a direct influence on innovation capability. Therefore, in the effort to enhance the performance of MSMEs in the culinary sector, MSME owners should consider expanding their entrepreneurial networks and strengthening entrepreneurial leadership.